Beyond depression a new approach to understanding and management - Dowrick, Christopher, 1951- (Oxford : Oxford University Press, 2009)
Christopher Dowrick takes a critical look at commonly held views about the diagnosis and management of depression. He argues that out belief in depression as a medical condition is based on some shaky theoretical and functional foundations.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Depression, Mental -- Diagnosis; Depression, Mental -- Treatment; Depression, Mental -- Social aspects